ANALISIS KEBUTUHAN LUAS TERMINAL PENUMPANG DAN ALTERNATIF TATA LETAK TERMINAL BANDAR UDARA HAJI HASAN AROEBOESMAN ENDE NUSA TENGGARA TIMUR - Hasna Aliyah Makarima Shalihah; Fahrur Rozi; Linda Winiasri (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In 2018 the airport Haji Hasan Aroeboesman East Nusa Tenggara Ende has a building area of the existing passenger terminal covering an area of 825 m2.With this area, the terminal building can accommodate flight service users of 200 thousand pax/year. In an effort to prevent the occurrence of passenger terminal conditions that are not able to accommodate the number of passengers in 2038, then in the terminal development plan it is necessary to analyze the needs of the passenger terminal area using data on the number of passengers within a period of 5 years (2014 - 2018). Forecasting the number of passengers in the next 20 years using the linear regression method. This method is also used to determine the number of passengers at busy times as a calculation of space requirements at the terminal. In addition, the SPSS Software uses a simple linear regression method. Simple linear regression analysis is a regression method that can be used as a statistical inference tool to determine the effect of an independent variable on the dependent variable. Forecasting passengers for the next 20 years begins in 2019 - 2038. The number of passengers during busy times was 216 departing passengers and 215 arriving passengers. With the total number of passengers busy departing and arriving, the predicted number of passengers will reach 500 thousand pax/year. For the number of passengers, the required building expansion is 1.372 m2. So the total broad needs of passenger terminal at the airport need Haji Hasan Aroeboesman East Nusa Tenggara Ende is 2.197 m2.